Nurses and nursing : the person and the profession - Ó Lúanaigh, Pádraig, MSc(Psych) (Routledge, 2017)
This textbook draws on international contributors with a range of backgrounds to explore, engage with and challenge readers in understanding the many aspects and elements that inform and influence contemporary nursing practice.
Keywords: ošetřovatelství; ošetřovatelky; zdravotní sestry; nursing; nurses; practical nurses; učebnice; elektronické knihy; textbooks; electronic books